A comparative study of stress experienced by Swedish and Norwegian police officers - Padyab, Mojgan; Hansson, Jonas; Sundqvist, Johanna; Inzunza, Miguel; Ghazinour, Mehdi (Frontiers in Health Services, 2023)
Police officers work in a variable environment under different circumstances and often involves stressful situations. This include working irregular hours, ongoing exposure to critical incidents, confrontations and violence. community police officers are mainly out in the society and have daily contact with the general public. critical incidents can also consist of being criticized and stigmatized as a police officer, both from the public but also lack of support from their own organization. There is evidence on negative impacts of stress on police officers. However, knowledge about the nature of police stress and its various types is insufficient. It is assumed that there are common stress factors which are universal among all police officers in different contexts but there is a lack of comparative studies to provide empirical evidence. The aim of this study is to compare different types of stress among police officers in Norway and Sweden and how the pattern of experiencing stress has changed over time in these countries. The study population consisted of patrolling police officers from 20 local police districts or units in all seven regions in Sweden (n=953) and patrolling police officers from four police districts in Norway (n=678). A 42-item Police Stress Identification Questionnaire was used to measure the stress level. The findings show differences in types of stressful events as well as its severity among police officers in Sweden and Norway. The level of stress decreased over time among Swedish police officers whereas it showed no change or even an increase among the Norwegian participants. The results of this study are relevant for policy-makers, police authorities and lay police officers in each country to tailor their efforts to prevent stress among police officers.